1995
DOI: 10.1111/j.1365-2141.1995.tb05303.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal natural killer (NK) cell lymphoma: report of a case with activated NK cells containing Epstein‐Barr virus and expressing CD21 antigen, and comparative studies of their phenotype and cytotoxicity with normal NK cells

Abstract: Malignant lymphomas arising from the nasal cavity have been considered to be derived from T cells, but recent surface marker studies suggest that more than half of the lymphomas are derived from natural killer (NK) cells. Here we describe a case of nasal lymphoma whose lymphoma cells were identified as NK cells by morphological, phenotypic, immunogenotypic, and functional studies. We believe this is the first study with functional evidence of NK activity. When compared with normal freshly isolated NK cells or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…In a workshop held recently to explore the definition and diagnosis of lymphomas presenting in the nose and other extranodal sites, a designation of nasal T/NK cell lymphoma was recommended for these lesions, emphasizing the expression of antigens associated with both T and NK cells . Though the cell origin of this subtype of lymphoma is still not clear, some studies have provided evidence that nasal T/NK cell lymphoma is derived from NK cells, rather than from T cells (Emile et al, 1996;Jaffe, 1996;Kaneko et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In a workshop held recently to explore the definition and diagnosis of lymphomas presenting in the nose and other extranodal sites, a designation of nasal T/NK cell lymphoma was recommended for these lesions, emphasizing the expression of antigens associated with both T and NK cells . Though the cell origin of this subtype of lymphoma is still not clear, some studies have provided evidence that nasal T/NK cell lymphoma is derived from NK cells, rather than from T cells (Emile et al, 1996;Jaffe, 1996;Kaneko et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Table 2 Phenotypic analysis of aggressive NK-cell leukemia cases Case no. CD2 CD16 CD56 CD57 CD3 CD4 CD5 CD7 CD8 CD25 HLA-DR Other specific markers EBV Aggressive NK-cell leukemia R Suzuki et al expression of CD16 was reported to be downregulated by activation 49 or administration of IL-2, 50 it is now recognized to represent functional NK-cell subsets. CD16 þ CD56 dim NK cells were first regarded as more mature form of NK cells, as compared with CD16 neg/dim CD56 bright NK cells.…”
mentioning
confidence: 99%
“…Persistent EBV infection is associated with various lymphoid and epithelial malignancies, including Burkitt lymphoma, Hodgkin lymphoma, peripheral T-cell lymphoma, and nasopharyngeal carcinoma (1,2). Recent reports suggest that the EBV infection is closely associated with mature natural killer (NK) cell malignancies (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the neoplastic NK cells possess monoclonal EBV genome, which indicates that latent EBV infection occurs before the clonal expansion (3)(4)(5). In almost all of the cases of nasal-type NK cell lymphomas, tumor cells contain EBV (6,7).…”
Section: Introductionmentioning
confidence: 99%